Recent Research Trends of Two‐Photon Photosensitizer for Simultaneous Imaging and Photodynamic Therapy. (27th July 2021) - Lee, Hyo Won; Lee, Dong Joon; Lim, Chang Su
Abstract : Imaging and photodynamic therapy through two‐photon excitation can be applied to medical application of deep inside the tissue by minimizing light absorption by the tissue. It is the best solution that can complement the shortcomings of conventional photodynamic therapy. In addition, auto‐fluorescence can be minimized, and damage to normal cells can be avoided through spatial and temporal control. To maximize the image realization and the effect of treatment, a single photosensitizer with high fluorescence quantum yields, two‐photon absorption value, and good 1 O2 or reactive oxygen species production performance must be developed. Therefore, recent research related to this topic is summarized. In addition, two‐photon photosensitizers that approach selective imaging and treatment for target diseases and future challenges were discussed. Abstract : Imaging and photodynamic therapy through two‐photon excitation can be applied deep inside of tissue, and it is the best solution to compensate for the limitation of conventional photodynamic therapy. To maximize the image realization and the effect of therapy, a photosensitizer with high value of two‐photon absorption cross sections, fluorescence quantum yields, and good 1 O2 or reactive oxygen species generation yield must be developed.